Isolated gross haematuria: A rare clinical presentation in neonate with urinary tract infection - Kayastha, Pawana; Basnet, Rydam; Adhikari, Ramesh Kant (Journal of Kathmandu Medical College, 2017)
Gross haematuria is uncommon in the fi rst month of life and etiologies of haematuria in the newborn is different from those in older children. we reported a six days old term male baby who was brought by parents with isolated complain of red colored urine for one day and his mother had culture positive urinary tract infection prior to delivery. The baby was diagnosed to have culture positive urinary tract infection. Our fi ndings suggest the diversity of clinical presentation of urinary tract infection in neonates and also some relationship between the history of urinary tract infection in mother and occurrence of urinary tract infection in neonate.